Nearest-neighbour distance, rather than group size, affects vigilance in urban flocks of preening Black-headed Gulls Chroicocephalus ridibundus. Issue 2 (3rd April 2021) - Novčić, Ivana; Vidović, Zoran
ABSTRACT: Capsule: The total flock size and number of nearby neighbours did not affect vigilance behaviour in the Black-headed Gull Chroicocephalus ridibundus, but an increase in the nearest neighbour distance had a positive effect on measures of vigilance. Aims: Vigilance allows animals to detect environmental stimuli, such as the presence of predators or competitors. Vigilance entails costs, however, because individuals may devote less time to other biologically important activities. We examined the trade-off between preening and vigilance in wintering Black-headed Gulls, while simultaneously considering the role of several confounding variables. Methods: Using multivariate regression models we examined the effect of several predictors on three common measures of vigilance: scan frequency, average scan duration, and the percentage of time allocated to scanning. Results: We did not detect a group-size effect on vigilance, but an increase in the nearest-neighbour distance had a positive effect on scanning frequency and the proportion of time focal gulls allocated to scanning. In addition, individuals at the periphery of flocks scanned their environment more frequently compared to centrally positioned gulls. Other variables that had significant effects on vigilance were location of roosting flocks, ambient temperature and wind speed. Conclusions: In general, this study indicates that antipredator vigilance played an important role in overall vigilance in preening gulls in an urban environment.